Modernism and Cultural Politics in Inter-war Austria: The Case of Clemens Holzmeister. (2021) - Rampley, Matthew
ABSTRACT: This article examines the work of the Austrian architect Clemens Holzmeister. A leading representative of Austrian architecture between the wars, and a significant figure in the i95os and i96os as teacher of the new generation of Austrian architects including Hans Hollein and Gustav Peichl, Holzmeister presents a perplexing image. In the i920s, he played an important role in the early architectural projects of Red Vienna, but in the following decade he endorsed the Austrofascist regime of Engelbert Dollfuß and Kurt Schuschnigg of i934-38. This article argues that his work presents other interpretative challenges too, for he was a prolific designer of churches, which have seldom been integrated into wider narratives of modern architecture. However his work is viewed, it was an important barometer of wider cultural and political currents in inter-war Austria, in particular the country's attempt to construct a meaningful identity after the collapse of the Habsburg empire. The aim of the article is not to rehabilitate or recover Holzmeister, but to consider the light his work casts on inter-war cultural politics in Austria, as well as the broader questions over the implicit value judgements that inform histories of modern architecture.